The competence of project team members and success factors with open innovation - Minjeong Oh; Sungyong Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The purpose of this paper is to examine the relationship between emotional, managerial, and intellectual competence of team members, which refer to the LDQ (Leadership Development Questionnaire) and impact on project success. (1) Background: Large and complex projects are being conducted in a dynamic business environment. The need for capabilities and managerial aspects of participants of the project for business performance increases. (2) Methods: A questionnaire survey was conducted on 164 project management professionals in various industries from Korea. The structural equation modeling technique was performed to establish the effect of competence of team members on project success factor. (3) Results: The results provided empirical support for the impact of team members' competencies on project success factor. Moreover, there is no difference in the perception of the impact of team members' competencies on project success factor, depending on their roles, such as project manager and team member. (4) Results: In this paper, the importance of the competence of team members in accordance with the project manager was presented. The findings of this study suggest the strategic direction of the members at this point when corporate innovation is needed.
Keywords: 650; competence; open innovation; project management; project success factor; project team member